Why Only Efficiency, and Not Efficacy, Matters in Psychotherapy Practice - Berg, Henrik (Frontiers in Psychology, 2021)
Evidence-based practice in psychology consists of two quality parameters. One of these quality parameters is efficacy and the other is efficiency. In this article, it is argued that the only relevant parameter for determining quality in clinical care is efficiency. Moreover, emphasising efficacy in psychotherapy practice is symptomatic of a scientocentric ideal in evidence-based practice in psychology. The proper understanding and use of scientific findings entail leaving this scientocentric ideal. In addition, it is crucial that efficiency is related to the ethical aims that constitutes psychotherapy practice.